The distribution of fake Australian vaccine digital certificates on an alt-tech platform - Childs, Andrew (Trends in organized crime, 2023)
This paper provides the first exploration of the online distribution of fake Australian COVID-19 vaccine certificates. Drawing on a collection of 2589 posts between five distributors and their community members on the alt-tech platform Gab, this study gathers key insights into the mechanics of illicit vaccine certificate distribution. The qualitative findings in this research demonstrate the various motivations and binding ideologies that underpinned this illicit distribution (e.g. anti-vaccine and anti-surveillance motivations); the unique cybercultural aspects of this online illicit network (e.g. ‘crowdsourcing’ the creation of fake vaccine passes); and how the online community was used to share information on the risks of engaging in this illicit service, setting the appropriate contexts of using fake vaccine passes, and the evasion of guardians in offline settings. Implications for future research in cybercrime, illicit networks, and organised crime in digital spaces are discussed.